Study on mechanical and friction properties of nano-Al2O3 as fluororubber additive. (December 2022) - He, Qiang; Wang, Guangfei; Zhang, Fangyuan; Li, Anling
Abstract: Fluorine rubber (FKM) has excellent high temperature resistance and corrosion resistance, but has poor mechanical properties and friction properties, which limits its application fields. In this work, the mechanical blending method was utilized to prepare fluororubber and nano-Al2 O3 /fluororubber. Then the mechanical properties and the normal and high temperature tribological behaviors were tested. Scanning electron microscope (SEM) and energy dispersive X-ray spectrum (EDS) were employed to investigate the effect of nano-Al2 O3 particles on the performance of fluororubber. The results show that nano-Al2 O3 particles as fillers improve the mechanical properties and friction and wear properties of fluororubber matrix. The improvement of fluororubber properties is due to the excellent interfacial bonding strength between nano-Al2 O3 particles and fluororubber matrix, and the improvement of the hardness and thermal conductivity of fluororubber matrix. Highlights: The mechanical properties of nano-Al2 O3 /fluororubber composites were studied. The wear behavior of nano-Al2 O3 /fluororubber composites was described. The wear mechanism of nano-Al2 O3 /fluororubber composites was investigated.